IDENTIFICATION OF FINE MOTOR SKILLS IN CHILDREN WITH INTELECTUAL DISABILITY - Joppy Nalurita Asgari; Dwi Aries Himawanto; Edy Legowo (JURNAL PENDIDIKAN DASAR, 2021)
Abstract: The purpose of this study was to describe fine motor skills in mentally retarded children. This study involved 20 mentally retarded children in special schools (SLB) in North Lombok. Identification was carried out using several data collection techniques, namely through observation, filling out instruments and interviewing the teacher. Identification of mentally disabled children focuses on several fine motor skills, namely: making curved lines, making horizontal lines, making circle patterns, cutting straight line pattern paper, cutting zigzag pattern paper, cutting circle pattern paper, cutting square pattern paper, simple drawing, coloring using colored pencils, coloring using crayons, and coloring using watercolors. The results of the study used descriptive analysis with two categorizations. Based on the results of the analysis, it was found that out of 20 mentally retarded children can be categorized as follows: on average 68% of children are in the Start Development category (MB), which means that children are starting to be able to do activities, but still with the help of teachers and 32% of children fall into the Developing Appropriate category Hope (BSH). Thus, through this identification it can improve fine motor skills in mentally retarded children by using other interesting methods or strategies. Keywords: skill, finemotor, intelectual disability